On obligations - Cicero (Oxford University Press, 2000)
On Obligations (De officiis) was written by Cicero in late 44 BC after the assassination of Julius Caesar to provide principles of behaviour for aspiring politicians. It explores the apparent tensions between honourable conduct and expediency in public life, and the right and wrong ways of attaining political leadership. The principles of honourable behaviour are based on the Stoic virtues of wisdom, justice, magnanimity, and propriety; in Cicero's view the intrinsically useful is always identical with the honourable.